2020
DOI: 10.18231/j.ijogr.2020.043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy following previous spontaneous abortion

Abstract: The objective of the present study was to study the pregnancy outcome following previous spontaneous abortion.The present study included 140 patients admitted in the department of Obstetrics and Gynaecology Government Medical College Srinagar, LD Hospital Jammu & Kashmir India from September 2018 to February 2019. Patients with history of spontaneous abortion preceding present pregnancy irrespective of gravidity, first visit or booked or unbooked were enrolled. Detailed history regarding previous abortion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been observed that incidence of spontaneous abortion is higher in urban than in rural areas. 1 Around 80% of spontaneous pregnancy loss occurs in early gestation. The incidence ranges from 11 to 22% in pregnancies of 5 to 20 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that incidence of spontaneous abortion is higher in urban than in rural areas. 1 Around 80% of spontaneous pregnancy loss occurs in early gestation. The incidence ranges from 11 to 22% in pregnancies of 5 to 20 weeks.…”
Section: Introductionmentioning
confidence: 99%